On some mechanical properties and wear behavior of sintered bronze based composites reinforced with some aluminides microadditives - Feldshtein, Eugene; Dyachkova, Larisa; Letsko, Andrey; Kiełek, P.; Kiełek, T. (Zielona Góra: Uniwersytet Zielonogórski)
In the paper, the changes in some mechanical properties and wear behavior of CuSn10 sintered bronze and MMCs based on this bronze reinforced with composite ultrafine aluminide powders FeAl/15% Al2O3, NiAl/15% Al2O3 and Ti-46Al-8Cr are described.
Keywords: metal-matrix composites (MMCs); mechanical properties; surface analysis; wear